Value-added utilization of high-temperature coal tar: A review. (15th May 2021) - Ma, Zhi-Hao; Wei, Xian-Yong; Liu, Guang-Hui; Liu, Fang-Jing; Zong, Zhi-Min
Graphical abstract: High-temperature coal tar is an important raw material for obtaining value-added aromatics. The comprehensive processing route for value-added utilization of HTCT was proposed. Coal tar research ideas are put forward in combination with future research directions. Highlights: High-temperature coal tar (HTCT) separation methods and upgrades were discussed. The utilization direction of coal tar pitch was elaborated in detail. Comprehensive processing route for value-added utilization of HTCT was proposed. Abstract: High-temperature coal tar (HTCT) is an important raw material for obtaining value-added aromatics. However, effective utilization of HTCT is not optimistic because of backward processing technology and higher energy consumption, resulting in fewer product types and lower purity. Accordingly, value-added utilization (VAU) of HTCT should be paid urgent attention. In order to realize VAU of HTCT, deep processing methods were systematically discussed. This paper mainly discusses the source, composition, research status, separation method, and upgrading of HTCT along with the utilization of coal tar pitch. Subsequently, the comprehensive processing route for VAU of HTCT was proposed. HTCT research ideas are put forward in combination with future research directions. We hope that this review will add to the ongoing discussions on the VAU of HTCT.